The effect of region of origin on the individual brands in the region: a study about São Roque and Vinícola Goés - Chiu, Annie Yu Teing (2020)
Regional marketing is an exercise that regions develop so that they can benefit from the region’s unique advantages and distinguish themselves from other regions. It happens in regions all around the world and with this marketing technique, these places can empower their brands and make the community stronger, it is also used by different industries. One problem that was not yet exploited by researchers is the relation between the region’s image as a wine producer and the individual brand equity of a company in the same region. To address this problem, the purpose of this study is exploring if an individual brand, Vinícola Goés, in a region, São Roque, can dislocate its image from the region’s negative image. To gather data, a survey was conducted with 100 respondents that followed Vinícola Goés on Instagram or that visited the area of São Roque and Vinícola Goés. The survey was conducted online and data lead to the study of the relations between Region’s Image as a wine producer, Perceived Quality of the region’s wine, Purchase Intention of the region’s wine and Brand Equity of an individual company in the region. Analyzing the relations between the variables it is possible to understand if a brand can dislocate its image from the region’s image and the variables that affect this relationship. This study may benefit companies in the wine industry, since the study analyzes the relationship between region of origin and brand equity, and therefore, these companies can understand if their investments in marketing will pay off if their product is segmented towards a different public than the region’s. Also, researchers and students in this field might be interested by the study since it brings a new component into the region of origin study.